Effects of two training workshops upon university students’ learning of critical thinking - Carlos Ossa Cornejo; Silva F. Rivas; Carlos Saiz Sánchez (PLoS ONE, 2025)
We evaluated the effect of two workshops on learning about critical thinking amongst first- year university students. 66 Chilean pedagogy students participated, all female, with ages ranging between 18 and 37 years. Two experimental groups were organized, one with direct teaching (n = 22) and another one with semi-directed teaching (n = 19), plus a control group (n = 25). Pre- and post-tests were applied with an abbreviated Pencrisal critical thinking questionnaire. The results showed statistically significant differences in both experimental groups between the pre- and post-test, with a greater difference in experimental group 1, while the control showed no significant differences. The covariables evaluated were age and academic performance upon entering university, observing that even after controlling for the aforementioned variables, there are differences between the experimental groups and the control. We discuss the possible positive effect of direct teaching in critical thinking as a more effective strategy.